Kikuchi–Fujimoto disease: a case report - Rahman, Mohammed Atiqur; Ferdousi, Kazi Rahila; Tonwi, Sabiha Afrin; Dey, Bishnu Pada; Chakrabortty, Rajashish (BIRDEM Medical Journal, 2026)
Kikuchi–Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis is a rare, benign, self-limiting disorder that typically presents with cervical lymphadenopathy and fever. Because of its clinical similarity to infectious, autoimmune or malignant conditions, misdiagnosis is common. We report a case of a 41-year-old male presenting with unilateral cervical lymphadenopathy, fever and night sweats. Excisional lymph node biopsy and histopathology revealed features consistent with KFD, including necrotizing lymphadenitis with karyorrhectic debris and crescentic histiocytes without neutrophilic infiltration. Awareness regarding KFD is essential for clinicians and pathologists to avoid unnecessary interventions such as prolonged antibiotic therapy or chemotherapy. Early histopathologically confirmation can significantly reduce patient morbidity and healthcare costs. BIRDEM Med J 2026; 16(1): 44-47